Knowledge, attitudes and practice of final-year student pharmacists in public health in Namibia, Zambia and Zimbabwe: an exploratory survey. (6th May 2018) - Law, Miranda G; Maposa, Prosper; Chambula, Elias; Steeb, David R; Eckel, Stephen F; Duncan, Gregory
Abstract: Objective: To explore the knowledge, attitudes and practice of final-year student pharmacists about public health. Methods: Knowledge, attitudes and practice of all final-year student pharmacists ( N = 158) in Namibia, Zambia and Zimbabwe were assessed through a quantitative 12-item survey. The survey assessed personal interest and attitude towards public health activities, self-assessed ability to perform basic public health activities, perspectives towards current pharmacist practices within public health activities in their country, and student involvement in public health activities during pharmacy school. Key findings: Eighty-two per cent of students responded to the survey ( n = 129). The majority (95%) of all final-year student pharmacists are interested in contributing to public health activities in both health promotion and disease prevention and feel, as pharmacists, they have the responsibility to do so. Additionally, the majority of students would like more education during pharmacy school on health promotion (93%) and disease prevention (89%). Despite their interest, low numbers of student pharmacists feel that pharmacists are currently utilised in disease prevention (35%) and health promotion (42%). Conclusion: Final-year student pharmacists in Namibia, Zambia and Zimbabwe express strong interest in public health education and involvement in public health activities. This interest and enthusiasm can serve as evidence for advancing public health education in the pharmacy curricula and for developing pharmacist opportunities in public health efforts that match the needs of the country.